Case Report: Design of a University of the District of Columbia (UDC) intrepid dynamic exoskeletal orthosis - Chen, Ji; Butler, J’niya; Nzonou, Mawussi; Thompson, Lara (Frontiers in Rehabilitation Sciences, 2025)
Intrepid Dynamic Exoskeletal Orthosis (IDEO), developed in Walter Reed National Military Medical Center (WRNMMC), is a custom, energy-storing orthosis made of carbon fiber. It is designed to improve mobility of individuals who have ankle dorsi and plantar flexor weakness. The development of IDEO follows a traditional workflow which is time consuming and costly. Users have reported functional limitations due to structural and material rigidity. This case report introduces a new IDEO design workflow which aims to achieve device functionality comparable to the IDEO from WRNMMC, and to reduce cost and time of production. Two IDEO prototypes were created. An experimental evaluation was conducted on a healthy participant wearing prototype 1 to assess the effects of IDEO on task completion time, joint angle and spatiotemporal measures. The participant walked along 3-meter straight line back and forth three times at self-selected speed in two conditions: walking without IDEO (baseline condition) and walking with IDEO. Our results show that the IDEO either hindered the movement or impaired the dynamic balance based on the current outcome measures, except that the range of motion of left ankle dorsi and plantar flexion angle was significantly reduced by 11 degrees (p value <0.001). Prototype 2 was created to compare time and cost of device production between UDC and WRNMMC workflows. The analysis shows that our approach reduced the cost and time. Further clinical evaluation is needed to assess the overall functionality of both prototypes when compared to the WRNMMC IDEO.